THE EFFECT OF PRODUCTS, PRICES, PROMOTIONS AND LOCATION ON THE INTEREST OF SAVING CITIZENS OF NAHDLIYIN IN SHARIA FINANCING SAVES AND LOANS COOPERATIVES BAITUL MAAL WA TAMWIL NUANSA UMAT KETAPANG BRANCH, SAMPANG MADURA, EAST JAVA - Lailatul Marom; Angga Dutahatmaja (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In the current era, the increasing competitive development of Islamic banking requires every bank to be nimble in attracting someone’s interest to save in the Islamic bank. Sharia products and services provided by sharia banks make it easier for customers to choose savings according to their needs and desires. This study aims to explain the effect of Product, Price, Promotion, and Location on the Interest of Saving Citizens of Nahdliyin in Sharia Financing Saves and Loans Cooperatives Baitul Maal Wa Tamwil Nuansa Umat Ketapang Branch, Sampang Madura, East Java. The data was collected through the distribution of questionnaires and carried out on 94 customer respondents. This research method is quantitative. The population in this study were customers of Sharia Financing Saves and Loans Cooperatives Baitul Maal Wa Tamwil Nuansa Umat Ketapang Branch, Sampang Madura, East Java who had been saving for 1 year. Data analysis in this study using SPSS version 25. Data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and analysis of determination. The hypothesis test used is the F test and t test. The results of the F-test hypothesis show that Product, Price, Promotion, and Location simultaneously have a significant effect on the Interest of Savings Citizens of Nahdliyin in Sharia Financing Saves and Loans Cooperatives Baitul Maal Wa Tamwil Nuansa Umat Ketapang Branch, Sampang Madura, East Java. The results of the t-test show that Product, Price, and Location variables have a significant effect on the Interest of Savings Citizens of Nahdliyin in Sharia Financing Saves and Loans Cooperatives Baitul Maal Wa Tamwil Nuansa Umat Ketapang Branch, Sampang Madura, East Java. While the Promotion variable has no significant effect on the Interest of Savings Citizens of Nahdliyin in Sharia Financing Saves and Loans Cooperatives Baitul Maal Wa Tamwil Nuansa Umat Ketapang Branch, Sampang Madura, East Java.